The Development of Waste Sorting Robot to Improve Environmental Care Attitudes at MTsN 1 Banda Aceh - Nurmahni Harahap (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
One of the waste management efforts is to sort waste. Waste handling in Indonesia, especially in Aceh, is still conventional. Based on these facts, a new breakthrough is needed during the era of the industrial revolution 4.0 by making a waste sorting robot. The purpose of this study was to determine the process of developing a waste sorting robot and to determine the environmental care attitude at MTsN 1 Banda Aceh by developing a waste sorting robot. This research method is Research and Development (RD). The researcher referred to Sugiyono's development model through 10 sequential steps (procedural), namely: Potential and problems; 2) data collection; 3) Product design; 4) Design validation; 5) Revised design; 6) Product trials; 7) Product revision; 8) Trial use; 9) Product revision; 10) Mass production. Research and development carried out by researchers only from steps 1-9. In the tenth step (10) of mass production, researchers did not do it because of time and cost constraints. The research location was conducted at MTsN 1 Banda Aceh. The research was carried out from October to November 2020. The research instruments were interview guides, a waste sorting robot product feasibility assessment questionnaire, and an environmental care attitude questionnaire. The data analysis technique used descriptive statistics with percentages. The results of the validation of the feasibility design of the waste sorting robot by 2 machine design experts and 1 science teacher at MTsN 1 Banda Aceh, an environmental material expert, obtained a score of 17 with a value of 100% in the less feasible category. Furthermore, in the trial, the score was 29 with a value of 100% in the very feasible category. The conclusion of this study is that the waste sorting robot is very feasible to use. The development of a waste sorting robot can improve environmental awareness at MTsN 1 Banda Aceh.